Inflammatory Biomarker Responses to Whole-Body Vibration in Subjects with Different Clinical Status: A Systematic Review - Moreira-Marconi, Eloá; Teixeira-Silva, Ygor; Meirelles, Alexandre Gonçalves de; Melo-Oliveira, Maria Eduarda de Souza; Santos, Aline Cristina Gomes; Reis-Silva, Aline; Paineiras-Domingos, Laisa Liane; Seixas, Aderito; Dionello, Carla da Fontoura; Sá-Caputo, Danúbia da Cunha de; Bernardo-Filho, Mario (International journal of environmental research and public health, 2022)
Background: Inflammation is considered to be a vital defense mechanism for health, acting as a protective response of the immune system through a satisfactory inflammatory biomarker response (IBR). IBR, as well as being beneficial to the organism, can be also responsible for a variety of chronic inflammatory diseases. Whole-body vibration (WBV) exercise is a type of physical exercise that can act on inflammation responses due its capacity for stimulating the sensory components that promote systemic responses. The objective of this study was to investigate the effects of WBV on IBR in different clinical status. Methods: This is a systematic review that includes randomized controlled trials (RCTs) on the effects of WBV exercise on IBR. The methodological quality, risk of bias, and level of evidence were rated. Results: Four RCTs met the selection criteria. The studies showed benefits associated with IBR (e.g., cytokines, adipokines, and C-reactive protein) in various clinical conditions, including healthy populations and some chronic diseases (such as obesity, aging disorders, and knee osteoarthritis), using several WBV protocols. Conclusions: WBV might be useful in the management of inflammatory conditions.